The mammals of Northern Melanesia: biogeography, systematics and ecology - Tyrone Hamilton Lavery (Frontiers of Biogeography, 2015)
Northern Melanesia's mammals are poorly known, and perceived deficiencies in faunal records and taxonomic descriptions have, until now, hindered detailed analyses. I examined aspects of biogeography, systematics and ecology in the region's mammalian faunas. Generalized linear models (GLMs) were used to test for differences in rates of persistence in four orders of mammal on continental shelf islands. Ochiai and endemism indices were used to delineate regions of high endemism and influential biogeographic boundaries. A non-parametric multivariate regression tree and GLMs were used to identify the influences of abiotic variables on mammalian species richness. Genetic sequencing, microsatellite genotyping, morphological and ecological data were used to determine evolutionary relationships among the widespread insectivorous bat family, Hipposideridae. Northern Melanesia’s islands support mammalian faunas that reflect the poor over-water dispersal abilities of non-volant mammals; lower rates of long- term persistence in dasyuromorphs and diprotodonts; pronounced diversification of the Family Pteropodidae; and comparative lack of speciation in insectivorous bat families. Analyses produced a clear hierarchical classification of Northern Melanesia’s islands based on their physical attributes and mammal assemblages, providing the first empirical analyses of Northern Melanesia’s and New Guinea’s mammalian zoogeography, and adding to biogeographic theory at both regional and local scales.